Malaria: Knowledge and prevention practices among school adolescents in a coastal community in Calabar, Nigeria - Ndifreke E. Udonwa; Abraham N. Gyuse; Aniekan J. Etokidem (AOSIS, 2010)
Background: Malaria prevention and treatment constitute an unbearable economic burden to most African countries, especially south of the Sahara, where about 500 million cases occur annually. The problem of malaria among adolescents has largely been overshadowed by the huge burden of the disease among young children. Attention to malaria among adolescents has also been diverted by the huge burden of HIV/AIDS among adolescents. Some surveys reveal a lack of knowledge and many misconceptions about the transmission and treatment of malaria, which could adversely affect malaria control measures and antimalarial therapy. Such a knowledge gap could have an adverse effect on school children, who could be used as change agents and as role models for their siblings and peers in the malaria control strategy. Objectives: To determine the malaria prevention practices of school adolescents in the coastal community of Calabar, Nigeria. Method: This was a cross-sectional survey involving secondary schools in southern Calabar. Four hundred adolescents were randomly selected from the 4565 learners in 5 out of 17 secondary schools in southern Calabar, Cross River State, Nigeria. A self-administered, semi-structured questionnaire was administered to the respondents. Results: Most respondents (77.5%) were aware that the vector transmits the malaria parasite through biting. Fewer respondents would prevent malaria attacks by clearing the vegetation in the peri-domestic environment (13.5%), filling up potholes (16.9%), opening up drainage (11%), using insecticide-treated nets (25.7%) or using antimalarial drugs (11.2%). Less than one-tenth (8%) would use various other methods such as not accepting unscreened blood, while only 11% obtained the information from their teachers. Conclusion: The study identified knowledge gaps among school children. There is a need to empower teachers with information about the cause of malaria and prevention strategies.